Peran Guru Kristen Sebagai Penuntun: Sebuah Kajian Teologis Efesus 4:11-16 Dalam Konteks Pendidikan Kristen [The Role of Christian Teachers as Guides: A Theological Study of Ephesians 4:11-16 in the Context of Christian Education] - Zega, Sri Susianti; Tarigan, Musa Sinar (Diligentia: Journal of Theology and Christian Education, 2024)
The role of teacher as a guide is very significant in teaching, especially to equip students to know God through Christian education. Teachers guide the students to understand knowledge, attitudes, skills, and spirituality based on Biblical principles. But in reality, teachers do not teach the Bible principles in learning, teachers do not guide the students, and have lack of knowledge of the Bible. Teachers should have understood the significance of guiding students based on the Bible. Hence, the purpose of writing this article is to present the significant role of teachers as a guide through the theological study based on Ephesians 4:11-16 for the context of Christian education with literature study as the research method. Teachers must guide students based on the truth of God's Word, through imitating Jesus as the Great Shepherd. Christian teachers’ role as guide do not only stop at knowledge in academic learning, but to be an impact for students to be a part of service to God and to build others up as members of the body of Christ. Christian teachers must guide students to achieve, namely: the unity of the faith in Christ as God and Savior in true knowledge, thorough maturity, and growth in accordance with the fullness of Christ and to ensure to be not tossed around by the waves of false teaching that ignore The Lord. This article concludes that the teacher's role as guide is one form for equipping students to grow more mature in Christ. The author suggests that Christian teachers understand that teachers are God's calling to reveal God's truth to students so that their lives base on Bible teaching, and Christian teachers must understand the students' needs to know God and grow spiritually to become more like Christ.BAHASA INDONESIA ABSTRACT: Peran guru sebagai pembimbing sangat penting dalam pengajaran, terutama untuk memperlengkapi murid-murid mengenal Tuhan melalui pendidikan Kristen. Guru membimbing murid untuk memahami pengetahuan, sikap, keterampilan, dan kerohanian berdasarkan prinsip-prinsip Alkitab. Namun pada kenyataannya, guru tidak mengajarkan prinsip-prinsip Alkitab dalam pembelajaran, guru tidak membimbing siswa, dan memiliki pengetahuan yang kurang tentang Alkitab. Seharusnya para guru memahami pentingnya membimbing murid berdasarkan Alkitab. Oleh karena itu, tujuan dari penulisan artikel ini adalah untuk memaparkan peran penting guru sebagai pembimbing melalui kajian teologis berdasarkan Efesus 4:11-16 dalam konteks pendidikan Kristen dengan metode studi literatur. Guru harus membimbing siswa berdasarkan kebenaran Firman Tuhan, dengan meneladani Yesus sebagai Gembala Agung. Peran guru Kristen sebagai pembimbing tidak hanya berhenti pada pengetahuan dalam pembelajaran akademis, tetapi menjadi dampak bagi siswa untuk menjadi bagian dari pelayanan kepada Tuhan dan membangun orang lain sebagai anggota tubuh Kristus. Guru Kristen harus membimbing murid-muridnya untuk mencapai, yaitu: kesatuan iman kepada Kristus sebagai Tuhan dan Juruselamat dalam pengetahuan yang benar, kedewasaan yang menyeluruh, dan pertumbuhan yang sesuai dengan kepenuhan Kristus serta memastikan agar tidak terombang-ambing oleh gelombang pengajaran palsu yang mengabaikan Tuhan. Artikel ini menyimpulkan bahwa peran guru sebagai pembimbing adalah salah satu bentuk untuk memperlengkapi murid-muridnya agar bertumbuh semakin dewasa di dalam Kristus. Penulis menyarankan agar para guru Kristen memahami bahwa guru adalah panggilan Tuhan untuk menyatakan kebenaran Tuhan kepada murid-muridnya agar hidup mereka didasarkan pada pengajaran Alkitab, dan guru Kristen harus memahami kebutuhan murid-muridnya untuk mengenal Tuhan dan bertumbuh secara rohani agar semakin serupa dengan Kristus.